2020
DOI: 10.1039/d0py01192d
|View full text |Cite|
|
Sign up to set email alerts
|

Non-thermal microwave effects in radical polymerization of bio-based terpenoid (meth)acrylates

Abstract: Microwave-assisted polymerization represents an opportunity to develop efficient polymerization strategies for the synthesis of (bio)macromolecules with improved properties. The possibilities will increase tremendously if non-thermal microwave effects, i.e. effect of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This frequent reorientation leads to the strong rotation, movement, agitation, collisions, and friction between species. 39–43 Subsequently, the supremacy of the MWA method can be described comprehensively by the dielectric properties and relaxation time of the reactants and solvents. 39–43 Dielectric constant ( ε r ) is a vital quantity to estimate and compute the reactivity of materials under the MW conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This frequent reorientation leads to the strong rotation, movement, agitation, collisions, and friction between species. 39–43 Subsequently, the supremacy of the MWA method can be described comprehensively by the dielectric properties and relaxation time of the reactants and solvents. 39–43 Dielectric constant ( ε r ) is a vital quantity to estimate and compute the reactivity of materials under the MW conditions.…”
Section: Resultsmentioning
confidence: 99%
“… 39–43 Subsequently, the supremacy of the MWA method can be described comprehensively by the dielectric properties and relaxation time of the reactants and solvents. 39–43 Dielectric constant ( ε r ) is a vital quantity to estimate and compute the reactivity of materials under the MW conditions. 40–42 According to the SS1 section and eqn (S1) mentioned in the ESI, † ε r can be calculated by using the dipole moment ( μ ) as an electronic descriptor which commonly describes the polarity of components and the distribution of the electrons on the molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwave is a cleaner and greener energy resource to drive the chemical reactions, and it has advantages in terms of extraordinary efficiency and high yield. The applications of microwave in chemical reactions are very wide, such as organic synthesis, biomass treatment, and nanomaterials. Most accelerating chemical reactions under the microwave irradiation can be explained by the microwave thermal effect. , Numerous experimental studies determine that not only the microwave thermal effect but also the microwave nonthermal effect play a decisive role in enhancing chemical reactions. Tiwari et al demonstrated the simultaneous activation of CH 4 and N 2 in a microwave catalytic reaction to produce NH 3 and C 2 products and found that the elementary reaction steps leading to NH 3 synthesis occurs due to the nonthermal effects of microwave irradiation. Silva et al verified that the combination of thermal and nonthermal effects during the microwave-assisted hydrothermal treatment provides ideal conditions for an efficient and rapid synthesis of pristine SrTiO 3 mesocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Silva et al 26 verified that the combination of thermal and nonthermal effects during the microwave-assisted hydrothermal treatment provides ideal conditions for an efficient and rapid synthesis of pristine SrTiO 3 mesocrystals. Castagnet et al 29 found a strong nonthermal microwave effect in the free radical polymerization of biobased terpenoid (meth)acrylates. Bichot et al 30 reported experimental study that addresses the nonthermal microwave effects on biomass by decoupling the heating effect from irradiation.…”
Section: Introductionmentioning
confidence: 99%